Relationship between Gene Dosage and Gene Expression in the Chloroplast of Chlamydomonas reinhardtii - Hosler, Jonathan P. (1989)
Expression of three chloroplast genes encoding proteins of different chloroplast complexes and the rRNA gene has been examined in cells having reduced numbers of chloroplast genomes as a result of growth in the presence of the thymidine analog 5-fluorodeoxyuridine. While accumulation of total mRNA for rpl2 (ribosomal protein L-1), rbcL (ribulose bisphosphate carboxylase large subunit) and atpA (α-subunit of ATP synthase) declined with gene copy number, the levels of translatable mRNA and rates of synthesis of these three proteins were largely unaffected. Accumulation of rRNA declined less precipitously than mRNA levels for the three proteins in response to the reduction in chloroplast genome number. Chlamydomonas appears to compensate for reductions in the number of chloroplast genomes at several different levels. Populations of cells with only one-fourth the wild-type amount of chloroplast DNA per cell on average have half the normal level of chloroplast ribosomes and nearly normal rates of CO(2) fixation and levels of specific chloroplast encoded proteins. These results suggest that normal cells accumulate a large excess of transcripts for chloroplast genes and that levels of expression of these genes are regulated by posttranscriptional mechanisms.